Microbial and Viral Genomic Diversity in Freshwater Environments - Silva Kavagutti, Vinicius (Jihočeská univerzita, 2023)
Most abundant microbes from natural environments remain uncultured as traditional culture approaches fail to sufficiently simulate native conditions. Moreover, the efforts to obtain axenic cultures are also hampered due to inter-microbial dependencies. The absence of cultured representatives has several downstream effects, e.g., little chance of experimentation and creating genetic models or hypothesis testing, phage isolation, or even producing complete, closed reference genomes. Lack of all these maintains severe gaps in our abilities to understand microbes in appropriate phylogenetic and ecological contexts and also their habitat at large. This thesis tries to circumvent these issues through a meticulous investigation of freshwater microbes and their viruses using a metagenomic approach in the Římov reservoir.
Microbial and Viral Genomic Diversity in Freshwater Environments
Microbial and Viral Genomic Diversity in Freshwater Environments